Social And Political Effects Of Pop Bali Alternatif On Balinese Society: The Example Of "Xxx" - Fushiki, Kaori (Penerbit Universiti Sains Malaysia (USM Press), 2013)
This article will clarify how the music genre "Pop Bali Alternatif" affects contemporary Balinese society, both socially and politically. The article focuses on the band "XXX" (Triple X), whose major hit "Puputan Badung" was released in 2006. Recent studies on the "Pop Bali" genre by Balinese researchers have divided it into two main streams: "Pop Bali Konventional" and "Pop Bali Alternatif." In contrast with the former, which is deeply connected with traditional Balinese music, "Pop Bali Alternatif" includes a variety of influences. For this reason, it exerts a powerful social influence, particularly on young people.